2019
DOI: 10.1016/j.neuroimage.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the human brain's cortical-subcortical functional network organization

Abstract: Understanding complex systems such as the human brain requires characterization of the system's architecture across multiple levels of organization-from neurons, to local circuits, to brain regions, and ultimately large-scale brain networks. Here we focus on characterizing the human brain's large-scale network organization, as it provides an overall framework for the organization of all other levels. We developed a highly principled approach to identify cortical network communities at the level of functional s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
634
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 446 publications
(677 citation statements)
references
References 104 publications
38
634
2
3
Order By: Relevance
“…However, in the secondary (HCP) dataset, there was approximately 0 correlation between subcortical ROIs and all other ROIs, including homotopic subcortical ROI pairs. The likely reason for this difference is due to poor temporal signal-to-noise ratio in the subcortex of HCP data (Ji et al, 2019), which we demonstrate here in SI Figure 4. Thus, we excluded the secondary dataset from all further analyses.…”
Section: Correlation Structure Replicates Across Datasetsmentioning
confidence: 90%
See 2 more Smart Citations
“…However, in the secondary (HCP) dataset, there was approximately 0 correlation between subcortical ROIs and all other ROIs, including homotopic subcortical ROI pairs. The likely reason for this difference is due to poor temporal signal-to-noise ratio in the subcortex of HCP data (Ji et al, 2019), which we demonstrate here in SI Figure 4. Thus, we excluded the secondary dataset from all further analyses.…”
Section: Correlation Structure Replicates Across Datasetsmentioning
confidence: 90%
“…The one major discrepancy was that in the subcortical portion of the matrix from the secondary (HCP) dataset, we observed correlations near zero. The reason for this observation is likely poor temporal signal-tonoise ratio (tSNR) in the subcortex of HCP data (Ji et al, 2019). Several factors may contribute to this poor tSNR.…”
Section: Functional Connectivity Of the Refined Rois Is Consistent Wimentioning
confidence: 99%
See 1 more Smart Citation
“…2c, there is branching of a community that is mostly expressed in the left hemisphere and includes Broca's area and the superior temporal gyrus, and bears resemblance to areas of activation during language processing tasks (Ji et al, 2019;Langs et al, 2015;Glasser et al, 2016a,b). This community, which has traditionally evaded most Power et al, 2011) (but not all (Ji et al, 2019;Langs et al, 2015)) mesoscale investigations, may represent a language system (Ji et al, 2019;Langs et al, 2015). It is notable that this putative language community is substantially more in agreement with the one described in Langs et al (2015) than Ji et al (2019), despite the fact that the former used a markedly different analytic approach (voxel-based, clustering in embedding space, etc).…”
Section: Discussionmentioning
confidence: 99%
“…Here clusters refer to communities, whereas in Yeo et al (2011), clusters were identified based on connectivity profiles. A recent study by Ji et al (2019), that used data from the HCP and the MMP cortical parcellation, identified an "oribito-affective" community that corresponds to posterior orbitofrontal parts of the limbic network descibed in Yeo et al (2011), though the authors note that it had the lowest "confidence score" of community assignment among the identified networks. Much of the nodes in the described orbito-affective community (i.e., posterior orbitofrontal) are included in our central executive community (Fig.…”
Section: Discussionmentioning
confidence: 99%